Solubility enhancement of diacerein through liquisolid technology: a formulation perspective - Nijhawan, Monika; Aleti, Rajeswari; Maramwar, Sravani; Vangala, Dedipya Goda Srivalli; Saxena, Trapti (Prospects in Pharmaceutical Sciences, 2025)
Liquisolid systems present an effective technique for improving the dissolution rate and oral bioavailability of poorly water-soluble drugs. The objective of this study is to formulate and evaluate diacerein liquisolid compacts using Tween 80 as the liquid vehicle, Neusilin and Fujicalin as carriers, and Aerosil 200 as a coating material. Sodium starch glycolate and magnesium stearate were used as disintegrants and lubricants, respectively. Pre- and post-compression parameters such as flow properties, hardness, friability, drug content, and disintegration time were measured. The in vitro release characteristics of the pure drug, marketed capsules (as reference), and liquisolid technique (test sample) were studied. Among all the formulations, FSC3 had the highest dissolving efficiency (DE) of 53.109% at 60 minutes, exceeding the marketed product's DE of 44.972%. FTIR analysis revealed no drug-excipient incompatibility, and all tested formulations fulfilled pharmacopeial requirements for flow and mechanical characteristics. Overall, the study demonstrates that the liquisolid technique significantly improves the dissolution of diacerein, indicating its potential to boost the physicochemical properties of poorly soluble drugs.